Towards a Pan African Business Simulation Game: Empowering Youth to Build Sustainable Business: Insights from EVER Virtual Internship in Africa - Cossa, G.; Issufo; Come; Sequeira (ISAGA 54th Anniversary Conference Simulation and Gaming for Social and Environmental Transitions, 2023)
Our presentation focused on the challenges faced by Africa's young population, primarily Generation Z, in gaining practical business experience due to a shortage of companies and organizations offering internships and other hands-on activities. Despite the proven didactic effectiveness of business games, they remain underutilized in the region. The EVER project, which we highlighted in our presentation, aims to bridge this gap. By leveraging the business simulation program, SPEE (Sistema de Práticas Empresariais e Empreendedorismo), the EVER project provides increased internship opportunities across diverse economic sectors in various African countries. This approach fosters a more comprehensive understanding of African business environments, transcending local realities. The interaction with the audience was incredibly encouraging. It became clear that we already have the seeds for a Pan African Business Simulation. All we need to do is put enough research and effort into nurturing this idea